(untitled) (The International Journal of Educational Sciences and Arts, 2023)
The article pinpoints the benefits, challenges, and proposed solutions of using artificial intelligence applications (AIP) in university education from the higher school administration diploma students’ perspective at the Ajloun National University (ANU). The descriptive analytical approach is used to achieve the related objectives. The questionnaire used as a research instrument is applied to a random sample of 81 male and female students, they were selected using the exhaustive method. The findings indicate that the benefits of using artificial intelligence applications in university education are of a high degree with a mean of (4.07). The results also show that among the challenges facing the use of artificial intelligence in university education is the high cost of implementing artificial intelligence applications in education. Given the findings, some solutions and recommendations are suggested to overcome the challenges facing the use of artificial intelligence, such as motivating faculty members to use artificial intelligence techniques in teaching and activating partnerships with the local community.